Self-directed learning in spoken grammar activities using poster presentation - Marlina, Neni; Dewi, Nita Sari Narulita; Supriyono , Yusup (Universitas Muhammadiyah Sidoarjo, 2020)
Looking for opportunities to let learners take charge of their learning autonomously is a pivotal responsibility for the teacher. This study aims at visualizing learners’ self-directed learning in grammar in spoken discourse classroom through poster presentation. Poster presentations which are given to a small group repeatedly has contribution to cultivate not only their speaking opportunities but also self-directed learning, , critical reflection, and independent action. A small group poster presenter consisting of 4 members is recruited as participants of the study. Learners’ journals and a 45 minute-video observation are analyzed using thematic analysis dealing with learners’ self-directed learning. The findings reveal that through poster presentation, the learners’ self-directed learning is portrayed as they select appropriate activities and strategies to present the material by searching from a number of resources, prepare their performance when they want to present, and handle questions or arguments from visitors. Those findings learners’ self-motivation, self- responsibility, and also self-management in learning. This study provides information that the learners should be given opportunities to experience learning meaningfully that fosters their learning autonomy to achieve meaningful learning success. HIGHLIGHTS: Learners need meaningful tasks that facilitate their learning autonomy. Poster presentation fosters learners’ motivation, self-responsibility, and self-management learning as foundations of learners’ self-directed learning. The use of poster presentations should continue to be used and developed in order to provide many benefits for learners.